The Advantages and Disadvantages of Offline and Emergency Remote Online General English Classes - Yuniastari, Rintya; da Silva, Anna Marietta (Universitas Negeri Semarang, 2022)
During the Covid-19 outbreak, with more than one billion school closures occurring worldwide, all teaching and learning interactions have to be conducted online, and it is a challenge for teachers (and learners) to adapt to this sudden shift because most educational institutions were not yet ready. However, regardless of the pandemic, in the era where technology plays a huge part in the advancement of human civilization, it is time for the global education system to evolve and begin incorporating technology into its implementation. Once the pandemic is over, teachers (and learners) will then have the opportunity to choose their medium of teaching and learning interactions, whether it is offline or online. Thus, this study examined and compared the advantages and disadvantages of both offline and emergency remote online teaching. The data were collected through Focus Group Discussion. Several prompts were used as discussion starters, but the researchers allowed the participants to share their opinions freely and let the data speak. The data were then analyzed and coded using thematic analysis. Researchers then made a summary of synthesis assumptions based on and supported by evidence from the data corpus. The findings revealed that teachers tend to favor offline teaching for its direct teacher-student interactions, although the high number of students in one class can be a challenge. Whereas online teaching is preferred for its time-efficiency and flexibility, albeit its technological complexity.